Using computer analysis of student writing to improve lesson planning - Fooks, Ian; Mohd. Asraf, Ratnawati (Asian EFL Journal Press, 2018)
This paper describes the results of a study that aimed to investigate the effectiveness of using Coh-Metrix to perform a computer analysis of student writing, and the extent to which this analysis could be used by the classroom teacher to improve lesson planning and thereby create opportunity for better learning outcomes. A quasi-experimental design was employed to gather data from undergraduate students taking a pre-requisite academic English writing course at a Malaysian public university. The students took part in four weekly lessons, during which the researchers assigned writing tasks that were analysed using Coh-Metrix to determine student performance in selected aspects of writing. Student essays were also independently assessed using the ESL Composition Profile. The results from the analyses of each assignment were then used to plan the following lesson. Following teaching that targeted identified areas of weakness, the majority of the selected writing measures analysed using Coh-Metrix showed an improvement from essay 1 to essay 3, as did the four categories assessed through the ESL Composition Profile. The results indicate that a Coh-Metrix analysis, used in conjunction with a teacher analysis of student writing, is useful in the identification of student needs and for the planning of appropriate classroom lessons.